FOLKLORE AS EDUCATIONAL ENTERTAINMENT MATERIALS IN KADAZANDUSUN LEARNING - Kiting, Rosliah; Dikul, Juni (Universitas Negeri Semarang, 2020)
Folklore is an ancient story that has become a special characteristic for every nation with diversity of cultures that embraces the cultural and historical richness of the nation. Usually the characters that appear in the folklore are in the form of animals, humans or gods. Generally, these folktales tell about an incident or the origin of a place. In this study, it focuses on the use of folklore as an educational entertainment in the classroom. The main method used to collect information is through a literature review by doing research from outside and within a country that is restricted to the educational entertainment of teaching and learning only. The finding of this study is that the use of folklore as a teaching material of educational entertainment can help students in increasing their interest and focus in the classroom. In fact, according to Rosliah Kiting, (2011), the use of storybook as a medium in Kadazandusun Language teaching and learning is able to enrich the vocabulary as well as inculcating of noble values that are very effective through adapting to the activities in the classroom. The use of folklore and the humorous elements encompassed in educational entertainment in the classroom will create excitement in learning sessions and the learning will be more interactive and focused.